2016
DOI: 10.3109/17518423.2015.1105320
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and clinical effects of botulinum toxin Type A combined with extracorporeal shock wave therapy on spastic muscles of children with cerebral palsy

Abstract: Our results support the hypothesis that the combined effects of BoNT-A and ESWT derive from their respective action on neurological and non-neural rheological components in spastic muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
1
20
0
3
Order By: Relevance
“…In the last five years, a few review studies have provided primary evidence to support the use of ESWT for the upper and lower limb spasticity: one meta-analysis of clinical trials on all types of spasticity in patients after brain injury, 40 two meta-analyses of randomized controlled trials (RCTs) on spasticity in post-stroke patients, 41,42 one narrative review on muscle hypertonia and dystonia, 43 and one authorized narrative review on upper and lower limb spasticity in post-stroke patients. 44 Additionally, several studies have confirmed utility of ESWT in reducing spasticity among patients with cerebral palsy (CP, 8 studies on the total sample of 124 patients, 4 used fESWT and 4 rESWT) [45][46][47][48][49][50][51][52] and multiple sclerosis (MS, 1 study involved a group of 34 patients treated with rESWT). 53…”
Section: Current Evidence On Shock Wavesmentioning
confidence: 99%
“…In the last five years, a few review studies have provided primary evidence to support the use of ESWT for the upper and lower limb spasticity: one meta-analysis of clinical trials on all types of spasticity in patients after brain injury, 40 two meta-analyses of randomized controlled trials (RCTs) on spasticity in post-stroke patients, 41,42 one narrative review on muscle hypertonia and dystonia, 43 and one authorized narrative review on upper and lower limb spasticity in post-stroke patients. 44 Additionally, several studies have confirmed utility of ESWT in reducing spasticity among patients with cerebral palsy (CP, 8 studies on the total sample of 124 patients, 4 used fESWT and 4 rESWT) [45][46][47][48][49][50][51][52] and multiple sclerosis (MS, 1 study involved a group of 34 patients treated with rESWT). 53…”
Section: Current Evidence On Shock Wavesmentioning
confidence: 99%
“…Sonoelastography was performed in the transverse view at the wrist and elbow for the median and ulnar nerves by applying vertical rhythmic compression with the transducer (the quality of the examination was guaranteed by the "optimal compression scale", a function of the sonoelastography software). On sonoelastography images, nerve hardness percentage was calculated in order to measure nerve stiffness (Picelli et al, 2017). The same physician (blinded to the other evaluations) examined all the patients.…”
Section: Ultrasonographic Evaluationmentioning
confidence: 99%
“…Moreover, they used the TE technique, which is operator dependent (because the stress applied can vary) and lacks precision in the color-coded graphic representation of stiffness. Picelli et al (13) in 2017 proved that the combination of botulinum toxin serotype A (BoNT-A) and ESWT (1 session per week for 3 weeks, 1500 SW per session, energy level 0.030 mJ/mm 2 , frequency 4 Hz) is more effective than BoNT-A alone for treatment of spasticity of different muscles in a group of 10 children with CP. Follow-up lasted 4 weeks and assessment of the stiffness was with SWE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that upregulated neovascularization (6), neuroregeneration (7), enzymatic activities (8), anti-inflammatory effect (9), and recruitment of endogenous mesenchymal stromal cells (MSCs) (10) might be involved in the process. Over the last few years several studies have found ESWT to be effective for treating muscle contractures in children with CP via its neuromodulatory and rheological effects (11)(12)(13)(14)(15). However, until now only subjective or operator-dependent assessment tools have been used in order to measure the effects of ESWT on spastic muscles.…”
mentioning
confidence: 99%